Urgensitas Pembelajaran Ilmu Hadis Di Era Digital - Abdul Wahid; Junida Junida (El-Sunan: Journal of Hadith and Religious Studies, 2023)
Hadith as the words of the Prophet SAW. from time to time is very interesting to study and study. Along with the rapid development of technology, it also influences the development of hadith studies. In this digital era, there are many hadith books that fill the media space. Technological developments have given birth to hadiths that can exist on social media. Various applications have been presented with attractive packaging so that the hadith problem which was previously done manually by having to open volumes of hadith books, now has a hadith application that makes it easier for users to find the hadith they need, even in the application there is also content -content such as sanad and matan. Among the hadith applications that have contributed to coloring in the digital era are: Maktabah Syamilah, Lidwa Pusaka, Gawamil Kaleem, Mausyu'ah and so on. Seeing the development of hadith itself which is now in the digital era, we should know how to take advantage of it. moreover, these academics are so enthusiastic about developing hadith studies in this digital era. Our role as regeneration is only to maximize it and develop it in order to develop the hirroh of hadith studies towards a golden era again. ABSTRAK Hadis sebagai sabda Nabi SAW. dari masa ke masa sangat menarik untuk dikaji dan dipelajari. Seiring dengan perkembangan teknologi yang melaju pesat juga mempengaruhi tehadap perkembangan kajian hadis. Di era digital ini, banyak ditemui kitabkitab hadis memenuhi ruang media. Perkembangan teknologi telah melahirkan hadis bisa eksis di media sosial. Berbagai aplikasi telah disajikan dengan kemasan menarik sehingga problem hadis yang tadinya dilakukan secara manual dengan harus membuka kitab-kitab hadis yang berjilid-jilid, kini telah hadir aplikasi hadis sehingga memudahkan bagi pengguna dalam mencari hadis yang dibutuhkan, bahkan di dalam aplikasi tersebut juga terdapat konten-konten seperti sanad dan matan. Di antara aplikasi hadis yang turut mewarnai di era digital adalah: Maktabah Syamilah, Lidwa Pusaka, Gawamil Kaleem, Mausyu’ah dan sebagainnya.Melihat perkembangan hadits sendiri yang sekarang sudah ber-Era digital maka sudah semestinya kita harus mengetahui bagaimana cara memanfaatkan hal itu, terlebih para akademi-akademisi tersebut sudah begitu bersemangat mengembangkan kajian hadits di era digital ini. Peran kita sebagai regenerasi hanyalah memaksimal mungkin dan mengembangkannya guna mengembangkan hirroh kajian hadits menuju era ke-emasan kembali.